Lithium-ion storage in honeycomb-structured biomass-derived porous carbon - NurulHuda, Shah; Ling, Jin Kiong; Bindhu, Devu; Ghufira, .; Izan Izwan, Misnon; Sreekala, Chandrasekharan Nair Omanaamma; Yang, Chun-Chen; Jose, Rajan (Elsevier, 2025)
Honeycomb-shaped porous carbon (HSPC) offers unique surface properties for rapid ion transport through the bulk and hence could deliver desirable electrochemical charge storage performance; however, their fabrication is through time and cost intensive sacrificial template methods. Herein, HSPC was synthesized from a carefully selected plant component (coconut rachis) containing a dense network of phloem and xylem. The synthesized activated carbon has relatively high carbon content (>80 %), desirable textural characteristics (specific surface area ~ 1290 m2⸱g−1 and pore diameter ~ 2.0 nm), and high edge-plane fraction (ratio between relative density of edge and basal plane ~0.26). The HSPC electrodes delivered specific capacitance up to ~126 F⸱g−1 at 100 mA⸱g−1 at a potential window of 2–4 V in the HSPC//LiPF6//Li lithium metal capacitor configuration and retained ~98 % of its initial capacity after 1000 cycles with coulombic efficiency ~100 %. The performance of the device has been validated by electrochemical impedance spectroscopy before and after cycling. A postmortem analysis confirmed structural and chemical stability of the device upon cycling.